1996
DOI: 10.1159/000217216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Molecular Weight Hydroxyethyl Starch (HES 40/0.5-0.55) on Hemostasis and Hemorheology

Abstract: Hydroxyethyl starch (HES) with a high or medium molecular weight (MW) and a high degree of substitution is difficult to degrade and leads to an accumulation of large molecules. These molecules have a negative effect on hemostasiological parameters. In 10 patients with cerebrovascular diseases, a hemodilution therapy was carried out with low MW HES for 10 days. Due to the low MW of the HES used (56-61 kD), the rheological parameters erythrocyte aggregation and plasma viscosity were significantly lowered (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
2
20
0
2
Order By: Relevance
“…The in vivo Mw for medium substituted HES (MS = 0.5) was measured around 60 kDa. Using HES (200/0.5) this in vivo Mw is reached quite fast after infusion [1]. The equilibrium of in vitro and in vivo Mw of HES (70/0.5) is random.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The in vivo Mw for medium substituted HES (MS = 0.5) was measured around 60 kDa. Using HES (200/0.5) this in vivo Mw is reached quite fast after infusion [1]. The equilibrium of in vitro and in vivo Mw of HES (70/0.5) is random.…”
Section: Discussionmentioning
confidence: 96%
“…A reference value for this amount of HES molecules is the Bf10% (10% of infused molecules are smaller than this molecular mass). Additionally, enzymatic degradation beginning from the outer molecular chains [1] is only possible in glycosidic bonds that are not substituted [6]. The splitting of parts of HES molecules is assumed to be representative for the whole molecule [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C2/C6 ratio describes the ratio of hydroxyethyl groups substituted at the C2 and C6 positions of the glucose molecules of starch. These characteristics are also important for the blood coagulation compromising potency [15] in that the higher the molecular weight [16,17], the higher the degree of substitution [18][19][20] and the higher the C2/C6 ratio [21], the greater is the effect of an HES solution on blood coagulation. The HES solutions investigated in the present study are identical with regard to molecular weight (200 000) and degree of substitution (0.5) but differ with regard to the C2/C6 ratio, in that potato starch derived HES has a C2/C6 ratio of 6.5 : 1 and corn starch derived HES has a C2/C6 ratio of 5.1 : 1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, when administering these substances, one has to take into account recent studies which have shown that dextrans and highly substituted hydroxyethyl starches, when they are used for a volume therapy lasting for several days, can lead to hemorrhagic complications. This can be avoided by using hydroxyethyl starch with a low in vivo MW (HES 200/0.5 or 70/0.5) [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%